A study of positive characteristics factors for teacher professional students in Bangkok - Prayai, Narulmon; Kramanon, Sittiporn (RMUTSB ACADEMIC JOURNAL (HUMANITIES AND SOCIAL SCIENCES), 2023)
The purpose of this research was to study the positive characteristic factors for teacher professional students in Bangkok. The sample was six hundred fifty-two students in the faculty of education by stratified random sampling. The instrument was the positive characteristics assessment form of teaching professional students, was the the rating scale with index of item-objective of 0.60-1.00, the discrimination range of 0.54-0.83, and reliability coefficient of 0.98. The statistics used were exploratory factor analysis and confirmatory factor analysis. The results of the research found that the positive characteristics of teacher professional students consisted of four factors: kindness, responsibility, love and faith in the teaching profession, and honesty, with the cumulative variance of 46.82%. The positive characteristic for teacher professional students measurement model was fit with empirical data ( =1.08, df=1 p=.30, GFI=1.00, AGFI=0.98, CFI=1.00, RMSEA=0.01, SRMR=0.01). Love and faith in the teaching profession had the highest standard weights (SC=0.98), followed by responsibility (SC=0.88), kindness (SC=0.78) and honesty (SC=0.68), respectively.